1991
DOI: 10.1111/j.1600-0404.1991.tb04707.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and neuro-otological study of homozygous beta-thalassemia under long-term desferrioxamine (DFO) treatment

Abstract: This report presents data on visual evoked potentials (VEPs) and brainstem auditory evoked potentials (BAEPs), as well as neurologic, ophthalmologic and otologic assessments performed on 120 patients with beta-thalassemia major undergoing long-term DFO treatment. A total of 32 patients showed abnormal VEPs and 14 abnormal BAEPs; seven had both VEP and BAEP abnormalities; 12 had sensorineural hearing loss (SNHL); 18 had conductive hearing loss, while 14 showed a combination of SNHL and conductive hearing loss. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…In addition to the ophthalmic and auditory neurotoxicity, sensorimotor neuropathy (paresthesias and weakness) [11], renal toxicity, moderate to severe pulmonary syndrome [1], growth retardation and bone abnormalities [12], local irritation at the site of subcutaneous infusion and allergic reactions have been reported in thalassemia patients receiving DFO. The reported rate of auditory toxicity varies widely in different studies [6, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ophthalmic and auditory neurotoxicity, sensorimotor neuropathy (paresthesias and weakness) [11], renal toxicity, moderate to severe pulmonary syndrome [1], growth retardation and bone abnormalities [12], local irritation at the site of subcutaneous infusion and allergic reactions have been reported in thalassemia patients receiving DFO. The reported rate of auditory toxicity varies widely in different studies [6, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted have involved transfusion-dependent patients on desferrioxamine; the increased latencies were mainly attributed to the neurotoxic effect of the latter. More specifically, as regards to BAEP and VEP, pathological rates are mentioned ranging between 0-25% and 3.1-32%, respectively [29][30][31][32][33][34]. Similar references involving nontransfused thalassemic patients do not exist to date.…”
Section: Discussionmentioning
confidence: 97%
“…Sensorineural hearing impairment was reported by Triantafyllou,et al in 12 patients (36.66%) from 44 patients, 22 whereas other studies reported sensorineural hearing impairment in all of patients with hearing impairment by BAEPs examination. [17][18][19] Previous studies by conventional audiometry, demonstrated sensorineural hearing impairment was higher compared to conductive hearing impairment 4,6,[8][9][10][11][12] Sensorineural hearing impairment in the current study was demonstrated in 94.74% patients from all of hearing impairment as well as the previous studies.…”
mentioning
confidence: 86%
“…21 Other BAEP studies reported between 12% to 36.6% patients. [17][18][19]22 This differrence results were probably as the result of the difference in methods.…”
Section: The Features Of Hearing Impairment In Thalassemia Majormentioning
confidence: 98%
See 1 more Smart Citation